Patterns of Valvular Involvement in Rheumatic Heart Disease patients taking Benzathine Penicillin at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Malla, Rabi; Thapaliya, Suman; Gurung, Prakash; Bogati, Amit; Khadka, Sunita; Shrestha, Sajana; Rajbhandari, Sujeeb; Adhikari, Chandra Mani (Nepalese Heart Journal, 2016)
Background and Aims: Acute rheumatic fever and rheumatic heart disease constitute an important public health problem in the developing countries. The disease results from an abnormal autoimmune response to a group A streptococcal infection in a susceptible host. We aim to describe the pattern of valvular involvement in patients taking Injection Benzathine Penicillin.Methods: All the patients, who were taking injection Benzathine penicillin during 15th April to 14th July, 2013 at our Centre, were included in this study. Demographic features like age, sex, echocardiographic diagnosis along with any adverse effects of Benzathine penicillin were collected.Results: A total of 661 patients were included in our study, out of which female predominated in numbers. Rheumatic heart disease rather than rheumatic fever was the cause for Penicillin injection. Mitral valve was the most common valve involved and it was more common in female.Pure mitral stenosis was the most common valvular involvement. Forty two percent patients underwent intervention; among them Percutaneous transluminal mitral commisuorotomy was the most common. There was no adverse event during the study time following penicillin injection.Conclusions: Women are more commonly affected than male. Mitral valve is the most common valve involved. Nepalese Heart Journal 2016; 13(2): 25-27